A systematic review on regenerative alveolar graft materials in clinical trials: Risk of bias and meta-analysis. Issue 1 (January 2022) - Alkaabi, S.A.; Alsabri, G.A.; NatsirKalla, D.S.; Alavi, S.A.; Mueller, W.E.G.; Forouzanfar, T.; Helder, M.N.
Abstract: Background: Alveolar cleft grafting is a necessary procedure to restore bone defects. Randomized clinical trials (RCTs) are regarded as a golden standard for investigating the efficacy of treatments. Nevertheless, risk of bias (RoB) can still affect the validity of these trials. We aimed to conduct a systemic review of all control trials (CTs) using regenerative materials for alveolar cleft reconstructions to evaluate their RoB and perform a meta-analysis of new bone formation. Methods: Cochrane Oral Health Group's Trials Register, the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (PubMed), EMBASE AND Google Scholar were searched up to October 2020. Thereafter, the articles underwent quality assessment (according to the Jadad scale and the Delphi list) for the evaluation of the RoB. Results: A total of 15 trials met the inclusion criteria, none of which reached a full score. Of these, 20% didn't randomize the trails, 73, 33% failed to describe the way of randomization, and none reported the double-blinded criteria. Furthermore, allocation concealment (99.9%), intention to treat (100%), and patient awareness (100%) were inadequately described. The meta-analysis found no significant difference between regenerative materials and iliac crest graft. Conclusion: This review showed high RoB in CTs implying quality improvement of CTs is necessary. Meta-analysis showed no significant difference between the regenerative materials and autogenous grafts.